The mummy, the will, and the crypt - Bellairs, John (Puffin Books, 2004)
Twelve-year old Johnny Dixon and his friend Professor Childermass look for the hidden will left by an eccentric cereal tycoon who wished to make life difficult for his heirs after his own death by suicide.